Oxysucrose polyaldehyde: A new hydrophilic crosslinking reagent for anti-crease finishing of cotton fabrics. (1st December 2019) - Lou, Jiangfei; Fan, Xuerong; Wang, Qiang; Wang, Ping; Yuan, Jiugang; Yu, Yuanyuan
Abstract: For the first time, oxidized sucrose (oxysucrose) was used as a hydrophilic crosslinking reagent instead of conventional anti-crease reagents for cotton fabrics. In this research, the partial oxidization of sucrose with sodium periodate generated multiple aldehydes, which acted as multifunctional cross-linkers and endowed cotton fabrics with anti-crease and hydrophilic function. The results showed that the oxysucrose-treated cotton fabrics obtained the maximum crease recovery angle of 245°, durable press rating of 3.0, and whiteness index of 82.8. Importantly, the oxysucrose-treated samples showed better hydrophilicity that overcomes the hydrophobization deficiency of anti-creased cotton fabrics treated with previously reported dimethylol dihydroxy ethylene urea (DMDHEU), glutaraldehyde (GA), and 1, 2, 3, 4, -butanetetracarboxylic acid (BTCA). The etherification reaction between the aldehyde group of oxysucrose and the hydroxyl group of cellulose was investigated and the possible crosslinking and anti-crease mechanism was proposed. Graphical abstract: Image 1 Highlights: Oxysucrose was a new anti-crease crosslinking agent. Crease resistance and hydrophilic property of cotton fabrics treated with oxysucrose were improved obviously. Etherification mechanism of oxysucrose and cellulose was proved.